2021
DOI: 10.48550/arxiv.2111.06314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proper Scoring Rules, Gradients, Divergences, and Entropies for Paths and Time Series

Abstract: Many forecasts consist not of point predictions but concern the evolution of quantities. For example, a central bank might predict the interest rates during the next quarter, an epidemiologist might predict trajectories of infection rates, a clinician might predict the behaviour of medical markers over the next day, etc. The situation is further complicated since these forecasts sometimes only concern the approximate "shape of the future evolution" or "order of events". Formally, such forecasts can be seen as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Our main result (Theorem 3.4) shows that RNN may be rewritten as a kernel method associated to the signature kernel K defined by (16). The proof is based on the neural ODE paradigm of Chen et al [32], who observed that infinite-depth residual neural networks exactly correspond to a specific type of ordinary differential equations (ODE), called neural ODE.…”
Section: Framing Rnn As a Kernel Methodsmentioning
confidence: 90%
“…Our main result (Theorem 3.4) shows that RNN may be rewritten as a kernel method associated to the signature kernel K defined by (16). The proof is based on the neural ODE paradigm of Chen et al [32], who observed that infinite-depth residual neural networks exactly correspond to a specific type of ordinary differential equations (ODE), called neural ODE.…”
Section: Framing Rnn As a Kernel Methodsmentioning
confidence: 90%